Concentrações de sacarose no desenvolvimento in vitro e na aclimatização de Cattleya loddigesii Lindley - Júnior, Renato Fernandes Galdiano [UNESP]; Mantovani, Cibele [UNESP]; De Faria, Ricardo Tadeu; De Macedo Lemos, Eliana Gertrudes [UNESP] (Universidade Estadual de Londrina, 2013)
This work aimed to study the influence of sucrose in the culture medium for in vitro growth and acclimatization of the epiphytic orchid Cattleya loddigesii. Five sucrose treatments (absence, 10, 20, 30 and 40g L-1) were used in a randomic experimental design. Mature seeds were sowed in 1/2 MS culture medium and after 90 days the plantlets (1.0 +/-0.2 cm) were inoculated between the treatments, whereby they were remained more 90 days. After 180 days of the beginning of the experiment the plantlets were removed from the flasks and evaluated the number of roots, shoot length, number of leafs, total dry weight and photosynthetic pigments. Survival percentage was evaluated after 75 days of acclimatization. The data of biometric variables were analyzed by Anovaand polynomial regression (p<0.05). Theothers data were submitted to the Anova and the means compared by the Tukey test (p<0.05). The sucrose concentration of 20g L-1 favored the in vitro growth in all evaluated parameters, showed higher production of chlorophyll a, total chlorophyll and carotenoids, in addition to increased survival under ex vitro condition. The sucrose concentration of 20g L-1 in the culture medium was the most efficient among the tested concentrations both for in vitro growth and ex vitro establishment of Cattleya loddigesii.
Sucrose concentrations in in vitro development and acclimatization of Cattleya loddigesii Lindley
Keywords: Brazilian orchid; Carbohydrate; Micropropagation